Profile of David Baker, Demis Hassabis, and John Jumper: 2024 Nobel laureates in Chemistry - Bonnie Berger; David S. Eisenberg (Proceedings of the National Academy of Sciences, 2026)
The 2024 Nobel Prize in Chemistry recognized revolutionary computational success in predicting protein structures from amino acid sequences and for designing amino acid sequences that fold into desired protein structures. The ultimate accomplishment emerged principally from two labs, applying distinct approaches, culminating four decades of effort by the community of protein scientists. The lab of David Baker at the University of Washington made protein design a reality by adapting methods of classical physical chemistry. Demis Hassabis and John Jumper in the Deep Mind division of Google applied co-evolution and AI methods to enable prediction of protein models remarkably close to experimentally determined structures and prediction of vast numbers of structures of proteins not yet experimentally studied.